2014
DOI: 10.1371/journal.ppat.1004167
|View full text |Cite
|
Sign up to set email alerts
|

The Triggering Receptor Expressed on Myeloid Cells 2 Inhibits Complement Component 1q Effector Mechanisms and Exerts Detrimental Effects during Pneumococcal Pneumonia

Abstract: Phagocytosis and inflammation within the lungs is crucial for host defense during bacterial pneumonia. Triggering receptor expressed on myeloid cells (TREM)-2 was proposed to negatively regulate TLR-mediated responses and enhance phagocytosis by macrophages, but the role of TREM-2 in respiratory tract infections is unknown. Here, we established the presence of TREM-2 on alveolar macrophages (AM) and explored the function of TREM-2 in the innate immune response to pneumococcal infection in vivo. Unexpectedly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 72 publications
2
64
0
Order By: Relevance
“…As previously discussed, the TREM2 gene is highly expressed in a subset of myeloid cell typesnamely, microglia in the CNS, osteoclasts in the bone, and other tissue-specific macrophages, including Kupffer cells, as well as alveolar, intestinal, and peritoneal macrophages [58,73,[90][91][92][93][94][95]. Bone marrow cells and blood monocytes express low to undetectable levels of TREM2, although expression can be induced upon differentiation of the former into macrophages or dendritic cells in vitro [50,87,91].…”
Section: Regulation Of Trem2 Gene Expressionmentioning
confidence: 94%
“…As previously discussed, the TREM2 gene is highly expressed in a subset of myeloid cell typesnamely, microglia in the CNS, osteoclasts in the bone, and other tissue-specific macrophages, including Kupffer cells, as well as alveolar, intestinal, and peritoneal macrophages [58,73,[90][91][92][93][94][95]. Bone marrow cells and blood monocytes express low to undetectable levels of TREM2, although expression can be induced upon differentiation of the former into macrophages or dendritic cells in vitro [50,87,91].…”
Section: Regulation Of Trem2 Gene Expressionmentioning
confidence: 94%
“…In contrast, alveolar macrophages isolated from TREM-2 −/− mice actually exhibited enhanced phagocytosis of E. coli and S. pneumonia associated with an increased level of complement component 1q (11). This may explain why TREM-2-deficient mice had a better survival rate than control wild-type mice following infection with S. pneumoniae (11). …”
Section: Trem-2 Functions and Therapeutic Applicationsmentioning
confidence: 97%
“…TREM-2 −/− mice experienced improved survival and enhanced bacterial clearance following infection with Streptococcus pneumoniae when compared to control wild-type mice (11). Moreover, macrophages isolated from TREM-2-deficient mice displayed greater induction of cytokines (i.e.…”
Section: Lessons From Genetic Mouse Modelsmentioning
confidence: 99%
“…For example, some studies have shown ectopic expression of TREM2 is sufficient to promote phagocytosis in non-myeloid cells [25, 122]. However a most interesting study from Knapp and colleagues demonstrated Trem2 deficiency had opposite effects on phagocytosis by bone marrow and alveolar macrophages [144]. In the context of neurodegenerative disease, it has often been assumed that TREM2 has a major role in phagocytosis of debris.…”
Section: Trem2 Function and Model For Ligand Engagementmentioning
confidence: 99%
“…TREM2 was reported to inhibit expression of C1q in alveolar macrophages [150] and C1q is expressed by microglia during development and improperly during AD to prune neuronal synapses [151]. …”
Section: Trem2 Function and Model For Ligand Engagementmentioning
confidence: 99%